Deaf sign language hidden in the fresco The Crucifixion of Saint Peter by Michelangelo Buonarroti (1475-1564): Michelangelo and deaf sign language - de Campos, Deivis; Buso, Luciano (Acta Biomedica Atenei Parmensis, 2020)
Since antiquity, specialists have worked to facilitate the communication of hearing impaired individuals, which according to the current literature, is among the disabilities that have the greatest impact on the quality of life. The system by which deaf people communicate is based essentially on sign language and the manual alphabet, employing gestures, and facial and body expressions. Although there is no exact data on how many people communicated through sign language in ancient times, studies show manual alphabets were used by deaf people in Europe in the early 15th century. Perhaps this was a reflection of a significant number of deaf people living throughout Europe at that time and who needed sign language to communicate. In this context, this manuscript, for the first time, demonstrates the renowned Italian Renaissance artist and genius of human anatomy Michelangelo Buonarroti (1475-1564) may have used deaf sign language in the fresco The Crucifixion of Saint Peter [Cappella Paolina, Vatican City, Italy]. This would demonstrate the engagement of one of the greatest Renaissance artists, with a clinical condition that has been studied by numerous health specialists since ancient times.